Review: Analisis Kualitatif dan Kuantitatif Kandungan Senyawa Kimia Herba Sasaladaan (Peperomia pellucida (L) H.B.K) - Fuji Fadhilla Sandy; Yasmiwar Susilawati; Zelika Mega Ramadhania (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
ABSTRACT Sasaladaan (Peperomia pellucida (L) H.B.K) is one of the medicinal plants in Indonesia which has many health benefits. Empirically used to treat fevers and headaches, while known pharmacological activities are antipyretic, analgesic, anti-inflammatory, antimicrobial, anti-cancer, antimalarial, and antidiabetic. This plant is prospective to be developed into standardized herbal medicine or phytopharmaca because it is easily obtained and its diverse pharmacological activities. The purpose of writing this review is to collect qualitative and quantitative analysis data of chemical compounds contained in herbal herbs. Analysis of previous research has included phytochemical screening, chromatographic patterns, determination of total phenol content, determination of total flavonoid content, determination of total alkaloid content, and identification of specific chemical compounds. Therefore, after knowing the content of the compound owned by the sasaladaan it is hoped that it can help other studies regarding the activity and development of the sasaladaan to be made as a standardized herbal medicine with guaranteed safety. Keyword: sasaladaan, quantitative analysis, quantitative analysis. ABSTRAK Sasaladaan (Peperomia pellucida (L) H.B.K) merupakan salah satu tumbuhan obat di Indonesia yang memiliki banyak khasiat untuk kesehatan. Secara empirik digunakan untuk mengobati demam dan sakit kepala, sedangkan aktivitas farmakologi yang telah diketahui adalah sebagai antipiretik, analgetik, antiinflamasi, antimikroba, anti kanker, antimalaria, dan antidiabetes. Tumbuhan ini prospektif untuk dikembangkan menjadi obat herbal terstandar atau fitofarmaka karena mudah diperoleh dan aktivitas farmakologinya yang beragam. Tujuan dari penulisan review ini adalah untuk menghimpun data analisis kualitatif dan kuantitatif senyawa kimia yang terkandung dalam herba sasaladaan. Analisis dari penelitian yang telah dilakukan sebelumnya meliputi skrining fitokimia, pola kromatografi, penetapan kandungan total fenol, penetapan kandungan total flavonoid, penetapan kandungan total alkaloid, dan identifikasi senyawa kimia spesifik. Oleh karena itu, setelah mengetahui kandungan senyawa yang dimiliki sasaladaan maka diharapkan dapat membantu penelitian-penelitian lain mengenai aktivitas dan perkembangan sasaladaan untuk dijadikan obat herbal yang terstandarisasi dengan keamanan yang terjamin. Kata kunci: sasaladaan, analisis kuatitatif, analisis kuantitatif.